A Survey of Sentiment Analysis based on Machine Learning Techniques - Jain, Riya; Dutt Choubey, Siddharth (International Journal of Computer Sciences and Engineering, 2025)
Internet has become a major part for every individual. More and more users are inclined to share their reviews on internet. This lead to a massive extent of data on web which require analysis so as to become useful. Extracting user’s perception from a large dataset of reviews is a difficult task. Sentiment analysis deals at analyzing user’s perception from this huge amount of reviews. The idea behind sentiment analysis aims at finding the polarity of text data and classify it into positive or negative. Machine Learning techniques proves to be very helpful in performing sentiment analysis task. This paper presents the survey of main techniques used for sentiment analysis and sentiment classification.